P01 The needs of caring relatives in relation to advance care planning. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Drewniak, D; Karzig, I; Krones, T
Abstract : Background: Relatives of patients in need of care and of those who are seriously ill assume a variety of tasks. The aim of this study is a systematic review on needs, chances, risks and barriers of care giving relatives regarding advance care planning (ACP). Methods: Qualitative and quantitative studies were identified through Pubmed, EMBASE, PsycINFO und CINAHL searches. In order to take into account that qualitative and quantitative studies were included, data were thematically synthesized. Results: In total 37 studies met inclusion criteria, including 24 quantitative- and 13 qualitative studies. Most studies originated from the USA (46%). Thematically, the studies can be divided into four different categories: "Attitudes towards ACP" showed that, even though relatives experience some uncertainty about the meaning of ACP, they mostly agree with the necessity of it. "Decision Conflicts" revealed that the level of congruence between relatives and patients is not given in many cases. Regarding the "Effectiveness of ACP" several studies highlighted the importance to consider family dynamics in the ACP process. Different "Barriers for ACP" were found, including a lack of knowledge and awareness about ACP and difficulties regarding the timing of ACP discussions. Conclusion: Although being an important group in the realm of ACP, as relatives are often also surrogate decision makers in case of incapability of decision making, studies on their attitudes and experiences are relatively rare and their knowledge seems quite limited albeit a perceived need for timely and appropriate ACP.